La sostenibilidad de la reforma económica en un caso "más probable": Perú - Arce, Moisés (2003)
A dominant chief Executive with a lengthy tenure, a rubber stamp legislature and increased business-government collaboration characterized the process of economic restructuring in Peru under Fujimori, and made the country the most likely candidate for deeper economic reforms. Nevertheless, the record of reform efforts was mixed. Departing from the tradition of previous scholarship, this article brings social interests back into the analysis of market transitions. It examines shifting governing coalitions, and the changing character of statebusiness interactions as countries move from the phase of crisis-induced reforms to the phase of consolidation of the reforms. The dominance of different groups across different phases of the economic restructuring process helps to account for the slowdown of the market agenda.